Growth, cycles and residential investment - Marcio Santetti; Michalis Nikiforos; Rudiger Von Arnim (The University of Utah, Department of Economics, 2022)
The empirical literature on neo-Goodwinian models of growth and distribution still lacks an explicit treatment of capital accumulation. Further, and across different theoretical approaches, residential investment is seen as a critical driver of the business cycle. This paper addresses these two issues. First, through four- and five-dimensional Structural Vector Autoregressive (SVAR) models, cyclical trajectories derived from impulse-response functions confirm profit-led demand and profit-squeeze distribution regimes, in accordance with the cyclical stylized facts in the vein of Goodwin (1967). Second, aggregate investment is then split into its residential and nonresidential categories. Results confirm that residential investment leads the cycle, whereas nonresidential investment lags it. Finally, this study argues that residential investment is, in reality, undertaken by corporations-and not households-, and can therefore not be seen as autonomous to the business cycle, demographics, and financial variables.
Keywords: E12; E22; E24; E25; E32; 330; Cyclical growth; Residential investment; Labor share of income